Stem water storage potential in plants of the Caatinga biome - Esmayle Alves de Tilesse, Francisco (Revista Ciência Agronômica, 2021)
Hydrological processes in forests are greatly infl uenced by existing plant species and their specifi c physiological characteristics. Water consumption by these plant communities is considered important in studies of water availability and water balance, especially in semi-arid regions. The aim of this study was to analyse water storage potential in the stems of representative plants of the Caatinga biome. The study was carried out in a preserved area of Caatinga in the Aiuaba Experimental Basin, Ceará, Brazil, where a phytosociological survey of the spatial distribution of wood density and stem water storage capacity was conducted. Allometric models were developed to estimate the active xylem area. Thirteen species and eight botanical families were registered during the fl oristic survey. The species with the highest density per hectare are the marmeleiro (Croton sonderianus Mull.) and the catingueira (Poicianella pyramidalis Tul.), reaching 85% of the total number of inventoried species. The water content in the stem of the catingueira is around fi ve times that of the marmeleiro; however, due to their greater occurrence in the area, the amount of water retained in the stem of marmeleiro plants (per hectare) is around twice that of the catingueira plants. After 40 years of conservation, the area is at a stage of secondary succession. The water potential of the species included in the survey is equal to about one fi fth of the maximum storage capacity of the reservoir that receives all the water drained from the basin.